Whitman’s Power of Visual Representation in Leaves of Grass: A Proto-Cinematic Gaze and the Influence of Modern Technology - Huang, Chiung-Ying (International Journal of Language and Literary Studies, 2024)
This paper discusses Whitman’s power of visual representation in Leaves of Grass, attempting to link the notion of a proto-cinematic gaze to a more general concern with the influence of modern technology on Whitman’s poetic vision. Whitman’s observation, like a camera producing the immediate photographic impression of the crowd, emerges as a form of collective memory or a corporeal perception of mass, and claims omnipresence in the poet’s visual activity that records the changing landscape of the United States. The central argument is based on two significant elements of Whitman’s poetics which help Leaves of Grass revolutionize American modern poetry: the flâneur and his camera eye. Through the flâneur’s camera eye, mixed with his special techniques of observation, Whitman’s reader is drawn to the poet’s astonishing combination of verbal and visual modes, which, though intensely lyrical, evokes the strength of poetic graphic power.